Preparation method and application of novel LBL marine biomass hydrogel composite membrane
By layer-by-layer polyion gelation assembly on the base membrane surface of the nanofiltration membrane, LBL marine biomass hydrogel composite membrane was prepared, which solved the shortcomings of the existing nanofiltration membrane when separating dyes and salts, achieved efficient separation and improved stain resistance, and used green and environmentally friendly materials, which were simple to operate and cost-effective.
Patent Information
- Application Number
- CN202510057161.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-14
AI Technical Summary
When existing nanofiltration membranes treat textile printing and dyeing wastewater, it is difficult to effectively separate dyes and salts, resulting in aggravation of dye pollution. The nanofiltration membrane prepared by traditional interface polymerization has poor permeability to divalent salts.
By layer-by-layer polyion gelation assembly on the base film surface, a loose LBL marine biomass hydrogel composite film was prepared, and a three-dimensional hydrogel separation layer was formed using chitosan quaternary ammonium salt and sodium alginate to achieve high retention rate of dyes and low-salt ion retention rate.
While ensuring high separation efficiency, the membrane can effectively intercept dye molecules and allow water molecules and salt ions to pass through, enhancing the membrane's anti-fouling performance, and adopting green and environmentally friendly marine biomass materials, which are simple to operate and cost-effective.
Smart Images

Figure CN119701662A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of separation membrane preparation and application, and specifically relates to a preparation method and application of a novel LBL marine biomass hydrogel composite membrane. Background Art
[0002] With the rapid development of the textile printing and dyeing industry, a large amount of dye wastewater is discharged all over the world. Dyes are toxic, and improper treatment of their wastewater will further aggravate environmental pollution and water resource crisis, and then endanger human health. Therefore, the efficient purification and reuse of dye wastewater is extremely important. Traditional treatment processes include: flocculation, adsorption, biodegradation, oxidation and other processes to treat textile wastewater. These technologies generally remove pollutants indiscriminately, or degrade large molecules into small molecules or ions, and it is difficult to truly distinguish "waste".
[0003] In order to improve the dyeing efficiency of the target dye, textile wastewater often contains high-salinity inorganic salts, usually up to 5-6wt% of sodium chloride or sodium sulfate. Extracting and reusing valuable components from dye wastewater is an important sustainable production concept. Obviously, both water-based dyes and inorganic salts are valuable resources, so their recycling is particularly important. Nanofiltration technology is a low-pressure driven filtration process. Because it can effectively separate dyes and salts from water, it can be used as a sustainable technology to effectively treat textile printing and dyeing wastewater. However, since nanofiltration membranes can effectively block water-based dye molecules and multivalent salts, nanofiltration membranes with a molecular weight of 200-1000Da are generally used. Nanofiltration membranes are pressure-driven membranes, and this drive undoubtedly makes dye pollution more serious, especially when filtering mixed solutions of dyes and salts.
[0004] However, the nanofiltration membrane prepared by conventional interfacial polymerization has a dense separation layer, which can effectively block the passage of dyes, but at the same time has poor permeability to salts, especially divalent salts. Therefore, the concept of loose nanofiltration membranes and tight ultrafiltration membrane composites was introduced into the separation of dyes and salts, which have larger pore sizes than typical NF membranes. At present, loose NF membranes and tight UF membranes have been developed to achieve effective separation of dyes and salts. Patents ZL202411078697.4 and ZL201910609824.1 prepare loose nanofiltration membranes by assembling on the surface of the base membrane and interfacial polymerization, which have high dye retention rate and low inorganic salt retention rate, and achieve efficient separation of dyes and salts.
[0005] Based on this, the present invention proposes a method to induce chitosan quaternary ammonium salt (CQAS) and sodium alginate (SA) to gel and assemble polyions layer by layer on the surface of the basement membrane to form a film, so as to prepare a loose LBL marine biomass hydrogel composite film. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide a novel method for preparing LBL marine biomass hydrogel composite membrane and its application. The method uses a clean ultrafiltration membrane as the base membrane, and the tris solution of marine biomass chitosan quaternary ammonium salt and sodium alginate is cross-linked and gelled and heat-treated on the surface of the base membrane for multiple times to obtain a hydrogel composite separation layer formed by self-assembly on the surface of the base membrane. The membrane has a high retention rate for dyes and a low retention rate for salt ions.
[0007] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a novel LBL marine biomass hydrogel composite membrane comprises the following steps: (1) Add chitosan quaternary ammonium salt into 0.1 M tris solution, heat and stir to obtain chitosan quaternary ammonium salt solution; (2) adding sodium alginate into 0.1 M tris solution, heating and stirring to obtain a sodium alginate solution; (3) Using the ultrafiltration membrane as the base membrane, firstly spread the chitosan quaternary ammonium salt solution on the surface of the base membrane, let it stand for a period of time, pour out the excess solution, and heat-treat it in an oven to obtain a 0.5 layer composite membrane; then spread the sodium alginate solution on the surface of the 0.5 layer composite membrane, let it stand for the same period of time, pour out the excess solution, and heat-treat it in an oven to obtain a layer of self-assembled hydrogel composite membrane; (4) Repeating step (3) multiple times on the surface of a layer of self-assembled hydrogel composite film obtained in step (3) to obtain a layer-by-layer self-assembled hydrogel composite film.
[0008] Furthermore, in step (1), the weight percentage of chitosan quaternary ammonium salt in the chitosan quaternary ammonium salt solution is 1wt% to 3wt%, the heating temperature is 60 to 80°C, the stirring speed is 1000 to 1500 rpm, and the stirring time is 6 to 10 hours.
[0009] Furthermore, in step (2), the weight percentage of sodium alginate in the sodium alginate solution is 1wt% to 3wt%, the heating temperature is 60 to 80°C, the stirring speed is 1000 to 1500 rpm, and the stirring time is 6 to 10 h.
[0010] Furthermore, in step (3), the chitosan quaternary ammonium salt solution is spread on the surface of the base film and allowed to stand for 5 to 15 minutes, the heat treatment temperature is 60 to 80° C., and the heat treatment time is 10 to 20 minutes.
[0011] Furthermore, in step (3), the sodium alginate solution is spread on the surface of 0.5 layer of composite film and allowed to stand for 5 to 15 minutes, the heat treatment temperature is 60 to 80° C., and the heat treatment time is 10 to 20 minutes.
[0012] Furthermore, in step (4), step (3) is repeated n times, where n is 0 to 6.
[0013] The novel LBL marine biomass hydrogel composite membrane is obtained by the above preparation method.
[0014] Application of the above-mentioned novel LBL marine biomass hydrogel composite membrane in dye wastewater treatment.
[0015] The hydrogel molecular structure contains a large number of hydrophilic groups, which can capture water molecules and form an organic repellent layer, and introduce a hydrogel layer with strong water binding ability on the surface of the separation membrane. Therefore, the membrane can have the performance of resisting dye pollution while ensuring high separation efficiency. The marine biomass material used in the present invention is green and environmentally friendly, and gels on the surface of the basement membrane to form a hydrogel separation layer with a three-dimensional network. Through layer-by-layer cross-linking, a smooth and defect-free separation layer can be formed on the surface of the basement membrane, and can be stably combined with the basement membrane. While effectively separating dyes and salt ions, the formed hydrogel hydration layer barrier can effectively enhance the anti-fouling performance of the membrane.
[0016] The present invention uses green and friendly marine biomass materials chitosan quaternary ammonium salt and sodium alginate with good biocompatibility as hydrogel substrates, and successfully prepares a surface uniform and efficient loose LBL hydrogel composite membrane on the surface of the basement membrane through an interfacial polyion gelation method. The three-dimensional hydrogel layer formed by layer-by-layer self-assembly on the surface of the composite membrane can effectively intercept dye molecules, but can allow water molecules and salt ions to pass through, and the charge on the surface of the composite membrane can further enhance the interception rate of dyes of the same ion type, and the outermost nuclear charge can be freely adjusted in terms of characteristic dye separation to achieve the purpose of efficient separation. In addition, the super-hydrophilic hydration layer on the membrane surface can effectively control the contamination of the membrane surface.
[0017] Compared with the prior art, the advantages of the present invention are: (1) Compared with the traditional hydrogel substrate, the present invention uses marine biomass materials chitosan quaternary ammonium salt and sodium alginate. These two materials are green and environmentally friendly. At the same time, introducing these two materials into the field of separation membrane preparation can increase the space for value-added utilization.
[0018] (2) The polyion gelation process of the present invention is more gentle, simple and easy to operate, and effectively avoids the cost problem caused by traditional methods.
[0019] (3) The present invention adopts a spaced layer-by-layer self-assembly preparation method, which can freely determine the charge of the membrane surface while ensuring the flux and retention rate, thereby further enhancing the separation efficiency of the membrane.
[0020] (4) The hydrogel layer on the surface of the composite membrane prepared by the present invention imparts hydrophilicity to the membrane, which can effectively enhance its anti-fouling performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Surface (a, c) and cross-section (b, d) SEM images of the LBL hydrogel composite films (1.0 and 3.0 layers) of Example 1 and Example 8.
[0022] Figure 2 This is a graph showing the surface Zeta potential characterization results of the PES base membrane, Examples 1-8 and Comparative Example 1.
[0023] Figure 3 These are test diagrams of surface water contact angles of PES base membranes, Examples 1-8 and Comparative Example 1.
[0024] Figure 4 Schematic diagram of the rejection rate and flux of the membrane prepared in Example 1 for different ions.
[0025] Figure 5 The flux and retention rate of Example 1 for different dye solutions. DETAILED DESCRIPTION
[0026] In order to make the purpose and technical solution of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention.
[0027] The preparation steps of 0.1 M tris solution in the following examples are as follows: About 400 mL of deionized water was added to 7.0 g of 3-(hydroxymethyl)aminomethane powder to fully dissolve it, and then transferred to a 1000 mL volumetric flask. Then, about 320 mL of 0.1 M HCl aqueous solution was added, and then 0.1 M HCl aqueous solution was slowly added dropwise to adjust the pH to 7. Finally, deionized water was added to make up the volume to obtain a 0.1 M tris solution.
[0028] Example 1 (1) 1.0 g of chitosan quaternary ammonium salt powder was added in batches to 99.0 g of 0.1 M tris solution and stirred and heated at 60 °C, 1000 rpm and 8 h to obtain a 1.0 wt% chitosan quaternary ammonium salt solution, recorded as solution A.
[0029] (2) 1.0 g of sodium alginate powder was added in batches to 99.0 g of 0.1 M tris solution and stirred and heated at 60 °C, 1000 rpm and 8 h to obtain a 1.0 wt% sodium alginate solution, which was recorded as solution B.
[0030] (3) A clean PES (polyethersulfone) base membrane was sandwiched between a grooved polytetrafluoroethylene frame and placed on a flat surface. Solution A was spread on the surface and allowed to stand for 15 min. The excess solution on the surface was then poured off and the membrane was placed in an oven at 80 °C for heat treatment for 10 min to obtain a 0.5-layer composite membrane.
[0031] (4) Then, solution B was spread on the surface of the above 0.5 layer composite film, and after standing for 15 min, the excess solution on the surface was poured off, and the film was placed in an oven at 80°C for heat treatment for 10 min to obtain a 1.0 layer LBL hydrogel composite film. Figure 1 It can be seen that a uniform and continuous hydrogel layer is formed on the membrane surface.
[0032] Example 2 (1) 1.5 g chitosan quaternary ammonium salt powder was added in batches to 98.5 g 0.1 M tris solution and heated and stirred at a heating temperature of 70 °C, a stirring speed of 1200 rpm, and a stirring time of 9 h to obtain a 1.5 wt% chitosan quaternary ammonium salt solution, which was recorded as solution A.
[0033] (2) Add 1.5 g of sodium alginate powder into 98.5 g of 0.1 M tris solution in batches and stir and heat at 70 °C, 1200 rpm and 9 h to obtain 1.5 wt% sodium alginate solution B.
[0034] (3) A clean PES-based membrane was sandwiched between a polytetrafluoroethylene frame with grooves and placed on a flat surface. Solution A was spread on the surface and allowed to stand for 15 min. The excess solution on the surface was then poured off and the membrane was placed in an oven at 80 °C for heat treatment for 15 min to obtain a 0.5-layer composite membrane.
[0035] (4) Solution B was then spread on the surface of the above 0.5 layer composite film. After standing for 15 min, the excess solution on the surface was poured off and the film was placed in an oven at 80 °C for heat treatment for 15 min to obtain a 1.0 layer LBL hydrogel composite film.
[0036] Example 3 (1) 1.0 g of chitosan quaternary ammonium salt powder was added in batches to the above 99.0 g of 0.1 M tris solution and stirred and heated at a heating temperature of 70 °C, a stirring speed of 1200 rpm, and a stirring time of 6 h to obtain a 1.0 wt% chitosan quaternary ammonium salt solution, which was recorded as solution A.
[0037] (2) 1.0 g of sodium alginate powder was added in batches to 99.0 g of 0.1 M tris solution and stirred and heated at 70 °C, 1200 rpm and 6 h to obtain a 1.0 wt% sodium alginate solution, which was recorded as solution B.
[0038] (3) A clean PES-based membrane was sandwiched between a polytetrafluoroethylene frame with grooves and placed on a flat surface. Solution A was spread on the surface and allowed to stand for 10 min. The excess solution on the surface was then poured off and the membrane was placed in an oven at 80 °C for heat treatment for 10 min to obtain a 0.5-layer composite membrane.
[0039] (4) Solution B was then spread on the surface of the above 0.5 layer composite film. After standing for 10 min, the excess solution on the surface was poured off and the film was placed in an oven at 80 °C for heat treatment for 10 min to obtain a 1.0 layer LBL hydrogel composite film.
[0040] Example 4 (1) 1.5 g chitosan quaternary ammonium salt powder was added in batches to 98.5 g 0.1 M tris solution and stirred and heated at 80 °C, 1200 rpm and 10 h to obtain a 1.5 wt% chitosan quaternary ammonium salt solution, recorded as solution A.
[0041] (2) Add 1.5 g of sodium alginate powder into 98.5 g of 0.1 M tris solution in batches and stir and heat at 80 °C, 1200 rpm and 10 h to obtain 1.5 wt% sodium alginate solution B.
[0042] (3) A clean PES-based membrane was sandwiched between a polytetrafluoroethylene frame with grooves and placed on a flat surface. Solution A was spread on the surface and allowed to stand for 10 min. The excess solution on the surface was then poured off and the membrane was placed in an oven at 70 °C for heat treatment for 15 min to obtain a 0.5-layer composite membrane.
[0043] (4) Solution B was then spread on the surface of the above 0.5 layer composite film. After standing for 15 min, the excess solution on the surface was poured off and the film was placed in an oven at 70 °C for heat treatment for 15 min to obtain a 1.0 layer LBL hydrogel composite film.
[0044] Example 5 This embodiment is the same as steps (1), (2), (3) and (4) of embodiment 1; solution A is spread again on the surface of the 1.0 layer of LBL hydrogel composite film, that is, the operation of step (3) is repeated once, and a 1.5 layer of LBL hydrogel composite film is obtained.
[0045] Example 6 In this embodiment, the steps (1), (2), (3) and (4) of the embodiment 1 are the same as those of the embodiment 1, and solution A and solution B are spread again on the surface of the 1.0-layer LBL hydrogel composite film, i.e., the operations of steps (3) and (4) are repeated to obtain a 2.0-layer LBL hydrogel composite film.
[0046] Example 7 Except for steps (5) and (6), the other steps of this embodiment are the same as steps (1), (2), (3) and (4) of embodiment 1.
[0047] (5) Spreading solution A and solution B again on the surface of the 1.0-layer LBL hydrogel composite film, i.e. repeating the operations of steps (3) and (4), to obtain a 2.0-layer LBL hydrogel composite film.
[0048] (6) Solution A is spread again on the surface of the 2.0-layer LBL hydrogel composite film, i.e., the operation of step (3) is repeated to obtain a 2.5-layer LBL hydrogel composite film.
[0049] Example 8 Except for steps (5), (6) and (7), the other steps of this embodiment are the same as steps (1), (2), (3) and (4) of embodiment 1.
[0050] (5) Spreading solution A and solution B again on the surface of the 1.0-layer LBL hydrogel composite film, i.e. repeating the operations of steps (3) and (4), to obtain a 2.0-layer LBL hydrogel composite film.
[0051] (6) Solution A is spread again on the surface of the 2.0-layer LBL hydrogel composite film, i.e., the operation of step (3) is repeated to obtain a 2.5-layer LBL hydrogel composite film.
[0052] (7) Spreading solution B again on the surface of the 2.5-layer LBL hydrogel composite film, i.e. repeating the operation of step (4), thus obtaining a 3.0-layer LBL hydrogel composite film. Figure 1 It can be seen that a uniform and continuous hydrogel layer is formed on the surface of the membrane, and the thickness is thicker than that of Example 1.
[0053] Comparative Example 1 This comparative example is the same as steps (1), (2) and (3) of Example 1, without any other steps.
[0054] The Zeta potential of the PES base membrane, Examples 1-8 and Comparative Example 1 was measured. The results are as follows: Figure 2 As shown, it indicates that the charge of the outer layer of the membrane surface can be freely adjusted.
[0055] The surface water contact angle test diagrams of PES base film, Examples 1-8 and Comparative Example 1 are as follows Figure 3 shown.
[0056] The LBL hydrogel composite film prepared in Example 1 was tested, and the results were as follows: Figure 4 and Figure 5 As shown: The membrane performance was evaluated using a cross-flow performance evaluation instrument (self-made in the laboratory), and the prepared membrane was pre-pressed at 0.2 MPa for 1 h to ensure the stability and validity of the measurement data. Figure 4 1000 ppm Na2SO4 (Z+ / Z-: 1 / 2), 1000 ppmNaCl (Z+ / Z-:1), 1000 ppmMgSO4 (Z+ / Z-: 1), and 1000 ppmMgCl2 (Z+ / Z-: 2) were used as the experimental salt solutions, and 200 ppm Congo red dye and various salt ion mixtures were prepared as simulated stock solutions to evaluate the flux and retention rate of the membrane. The experimental results showed that the membrane had an extremely low retention rate for salt ions, while a higher retention rate for Congo red dye, indicating that the LBL hydrogel composite membrane has good separation performance. Figure 5 In Example 1, 200 ppm of different dye solutions were used as feed solutions, and the flux and retention rate of the membrane were tested at 0.2 Mpa. The results showed that the LBL hydrogel composite membrane had high separation performance for these dyes. The retention rates and fluxes of 200 ppm Congo red of Examples 1-8 and Comparative Example 1 were also compared, and the results are listed in Table 1. The formula used in the above test is as follows; (1) F——membrane flux (L·m −2 ·h −1 ); V——water production volume (L); Δt——water production time (h).
[0057] (2) R——retention rate (%); C p - concentration of the permeate; C f ——Concentration of feed liquid.
[0058] Table 1 Retention rate and flux of 200 ppm Congo red in Examples 1-8 and Comparative Example 1 As shown in Table 1, the flux and retention rate of the membranes obtained in Examples 1-4 are both high, and the membrane flux obtained in Comparative Example 1 is large, and the single retention rate is extremely low, because no self-assembly is performed in Comparative Example 1. At the same time, as the number of self-assembly layers increases, it can be seen from Examples 5-8 that the retention rate of the membrane increases slightly, but it will cause a loss of flux.
[0059] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a novel LBL marine biomass hydrogel composite membrane, characterized in that: The steps include: (1) Add chitosan quaternary ammonium salt into 0.1 M tris solution, heat and stir to obtain chitosan quaternary ammonium salt solution; (2) adding sodium alginate into 0.1 M tris solution, heating and stirring to obtain a sodium alginate solution; (3) Using an ultrafiltration membrane as the base membrane, first spread a chitosan quaternary ammonium salt solution on the surface of the base membrane, pour off the excess solution after standing, and obtain a 0.5 layer composite membrane after heat treatment in an oven; The sodium alginate solution was spread on the surface of 0.5 layer of composite film, and the excess solution was poured out after standing for the same time, and then heat-treated in an oven to obtain a layer of self-assembled hydrogel composite film; (4) Repeating step (3) multiple times on the surface of a layer of self-assembled hydrogel composite film obtained in step (3) to obtain a layer-by-layer self-assembled hydrogel composite film.
2. The method for preparing the novel LBL marine biomass hydrogel composite membrane according to claim 1, characterized in that: The weight percentage of chitosan quaternary ammonium salt in the chitosan quaternary ammonium salt solution in step (1) is 1wt% to 3wt%, the heating temperature is 60 to 80°C, the stirring speed is 1000 to 1500 rpm, and the stirring time is 6 to 10 h.
3. The method for preparing the novel LBL marine biomass hydrogel composite membrane according to claim 1, characterized in that: The weight percentage of sodium alginate in the sodium alginate solution in step (2) is 1wt% to 3wt%, the heating temperature is 60 to 80°C, the stirring speed is 1000 to 1500 rpm, and the stirring time is 6 to 10 h.
4. The method for preparing the novel LBL marine biomass hydrogel composite membrane according to claim 1, characterized in that: In step (3), the chitosan quaternary ammonium salt solution is spread on the surface of the basement membrane and allowed to stand for 5 to 15 minutes, the heat treatment temperature is 60 to 80° C., and the heat treatment time is 10 to 20 minutes.
5. The method for preparing the novel LBL marine biomass hydrogel composite membrane according to claim 1, characterized in that: In step (3), the sodium alginate solution is spread on the surface of 0.5 layer of composite film and allowed to stand for 5 to 15 minutes. The heat treatment temperature is 60 to 80° C. and the heat treatment time is 10 to 20 minutes.
6. The method for preparing a novel LBL marine biomass hydrogel composite membrane according to claim 1, characterized in that: In step (4), step (3) is repeated n times, where n is 0 to 6.
7. A novel LBL marine biomass hydrogel composite membrane is obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the novel LBL marine biomass hydrogel composite membrane as claimed in claim 7 in dye wastewater treatment.
Citation Information
Patent Citations
Method for preparing loose nanofiltration membrane based on interfacial polymerization
CN110180402A
Dye / salt separation loose nanofiltration membrane based on aminated nano-diamond-polyphenol-metal network as well as preparation method and application of dye / salt separation loose nanofiltration membrane
CN118904119A
Sodium alginate / chitosan quaternary ammonium salt magnetic adsorption gel ball as well as preparation method and application thereof
CN112844328A
Method for composite treatment of polluted water by algae-chitosan and derivatives thereof
CN113526679A
Chitosan quaternary ammonium salt sodium alginate hydrogel as well as preparation method and application thereof
CN116239801A